Magnetic nano noble metal catalyst and preparation method thereof, method for preparing hydrogenated butadiene-acrylonitrile rubber, hydrogenated butadiene-acrylonitrile rubber and application of hydrogenated butadiene-acrylonitrile rubber

By using magnetic nano-precious metal catalysts, the problem of difficulty in the catalyst being easily shedded and separated when recycled in hydrogenated nitrile production is solved, and efficient hydrogenation of nitrile production and catalyst stability is achieved, and the hydrogenation of products is improved degree and wide application.

CN119158591APending Publication Date: 2024-12-20CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310706186.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing hydrogenated nitrile products are prone to falling off and difficult to separate when the catalyst is recycled during the production process. The active components are easily shedded and difficult to separate. The precious metals remain in the hydrogenation products, which affects the aging performance of the product and limits the mass production and wide application of hydrogenated nitrile.

Method used

Magnetic nano-precious metal catalyst is used, which consists of a support and metal components supported on the surface of the support. The support contains SiO2 coating layer and functional groups. Through the complexation of the coating and functional compounds, the stability of the recycling of the catalyst is improved. Sex and separation convenience.

Benefits of technology

The stability and efficient separation of precious metal components during recycling are achieved, the hydrogenation degree and catalytic activity of hydrogenated nitrile are improved, and the long-term stability and efficient performance of the catalyst are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004287430980000151
    Figure BDA0004287430980000151
  • Figure BDA0004287430980000161
    Figure BDA0004287430980000161
  • Figure BDA0004287430980000171
    Figure BDA0004287430980000171
Patent Text Reader

Abstract

The invention relates to the field of unsaturated copolymer hydrogenation, in particular to a magnetic nano noble metal catalyst and a preparation method thereof, a method for preparing hydrogenated butadiene-acrylonitrile rubber and application thereof, and hydrogenated butadiene-acrylonitrile rubber. The magnetic nano noble metal catalyst comprises a carrier and a metal component loaded on the surface of the carrier, the carrier comprises a matrix and a coating layer; wherein the substrate is made of magnetic nanoparticles, and the coating layer is made of SiO2; the surface of the carrier is grafted with a functional group; the magnetic nano noble metal catalyst is used for hydrogenation reaction of nitrile rubber. The magnetic nano noble metal catalyst comprises a carrier and a metal component loaded on the surface of the carrier, the carrier contains magnetic nanoparticles coated by a coating layer, and functional groups are grafted on the surface of the carrier, so that the magnetic nano noble metal catalyst has relatively high catalytic activity, is easy to separate and has excellent recycling stability; the average particle size of the magnetic nano noble metal catalyst is proper, the magnetic nano noble metal catalyst is difficult to agglomerate, and the contact efficiency with reactants can be improved, so that the catalytic efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of unsaturated copolymer hydrogenation, and in particular to a magnetic nano noble metal catalyst and a preparation method thereof, a method for preparing hydrogenated nitrile rubber, hydrogenated nitrile rubber and applications thereof. Background Art

[0002] Hydrogenated nitrile rubber has good properties such as wear resistance, low temperature resistance (-40℃), oxidation resistance, ozone resistance and thermal stability. It can be used to manufacture parts of automobile fuel systems, oil field blowout preventers, seals for nuclear power plants and printing and dyeing rubber rollers, etc. It is currently mainly produced through hydrogenation modification of nitrile rubber.

[0003] At present, most hydrogenated nitrile products on the market are produced by homogeneous solution hydrogenation. The homogeneous catalyst used is expensive and has poor stability. Because it is dispersed in the polymer solution in molecular form, it is difficult to separate the catalyst and the hydrogenation product. If the catalyst remains in the rubber product, it will seriously affect its aging performance. The above factors greatly restrict the mass production and wide application of hydrogenated nitrile. Compared with homogeneous solution hydrogenation, in the heterogeneous solution hydrogenation system, the catalyst and the hydrogenation product are easy to separate, which can effectively avoid the residue of precious metals in the hydrogenation product, and has a good industrial prospect.

[0004] Heterogeneous solution hydrogenation catalysts are generally prepared by loading precious metals on carriers such as silicon dioxide, carbon black, and titanium dioxide by methods such as impregnation, sedimentation, reduction precipitation, and complexing agent removal. The smaller the catalyst particle size, the larger the contact area with the reactants, and the higher the catalytic efficiency. However, if the catalyst particles are too small, they tend to agglomerate and it is difficult to separate and recover the catalyst after the reaction. The conventional loading method does not hold the precious metals firmly on the carrier, and some of them will be lost during recycling, which is not conducive to saving resources and reducing costs. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems in the prior art that active components are easy to fall off and difficult to separate when the catalyst is recycled, and to provide a magnetic nano noble metal catalyst and a preparation method thereof, a method for preparing hydrogenated nitrile rubber, hydrogenated nitrile rubber and applications thereof. The magnetic nano noble metal catalyst comprises a carrier and a metal component loaded on the surface of the carrier, and the carrier contains magnetic nano particles coated with a coating layer, and functional groups are grafted on the surface of the carrier, so the catalyst has high catalytic activity and is easy to separate.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a magnetic nano-precious metal catalyst, characterized in that the magnetic nano-precious metal catalyst comprises a carrier and a precious metal component loaded on the surface of the carrier;

[0007] The carrier comprises a substrate and a coating layer;

[0008] Wherein, the matrix is ​​magnetic nanoparticles, and the coating layer is SiO 2 ;

[0009] The surface of the carrier is grafted with functional groups;

[0010] Wherein, the average particle size of the magnetic nano noble metal catalyst is 30-100nm;

[0011] The magnetic nano noble metal catalyst is used for hydrogenation reaction of nitrile rubber.

[0012] The second aspect of the present invention provides a method for preparing a magnetic nano-precious metal catalyst, characterized in that the method comprises:

[0013] S1, coating the magnetic nanoparticles with a coating agent to obtain magnetic composite nanoparticles;

[0014] S2. reacting the magnetic composite nanoparticles, coupling agent and functional compound in the presence of a solvent to obtain functional magnetic composite nanoparticles;

[0015] S3, contacting the functional magnetic composite nanoparticles with a metal source to obtain a magnetic nano noble metal catalyst.

[0016] The third aspect of the present invention provides a method for preparing hydrogenated nitrile rubber, characterized in that the method comprises: contacting nitrile rubber glue, a magnetic nano-precious metal catalyst and a phosphine ligand, and performing a hydrogenation reaction to obtain a hydrogenated nitrile rubber glue;

[0017] Wherein, the magnetic nano noble metal catalyst is the magnetic nano noble metal catalyst provided by the first aspect of the present invention or the magnetic nano noble metal catalyst prepared by the method provided by the second aspect of the present invention;

[0018] The content of the noble metal element in the magnetic nano noble metal catalyst is 0.008-0.03wt% of the dry nitrile rubber.

[0019] The fourth aspect of the present invention provides a hydrogenated nitrile rubber prepared by the method provided by the third aspect of the present invention, characterized in that when the magnetic nano noble metal catalyst is used once, the hydrogenation degree of the hydrogenated nitrile rubber is not less than 80%.

[0020] According to one embodiment of the present invention, when the magnetic nano noble metal catalyst is used 10 times, the hydrogenation degree of the hydrogenated nitrile rubber is not less than 80%.

[0021] The fifth aspect provides an application of the hydrogenated nitrile rubber described in the fourth aspect of the present invention in at least one of the fields of aerospace, oil fields, transportation and deep sea.

[0022] Through the above technical scheme, the magnetic nano precious metal catalyst and its preparation method, the method for preparing hydrogenated nitrile rubber, the hydrogenated nitrile rubber and its application provided by the present invention achieve the following technical effects: the precious metal components are adsorbed by complexing reaction with functional groups, and will not cause the loss of metal components during the recycling process, have excellent recycling stability, and have high hydrogenation activity.

[0023] Furthermore, since the magnetic nano-precious metal catalyst is coated with magnetic nano-particles, the magnetic nano-precious metal catalyst can be separated from the reaction system by magnetic separation. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] The first aspect of the present invention provides a magnetic nano-precious metal catalyst, characterized in that the magnetic nano-precious metal catalyst comprises a carrier and a precious metal component loaded on the surface of the carrier;

[0026] The carrier comprises a substrate and a coating layer;

[0027] Wherein, the matrix is ​​magnetic nanoparticles, and the coating layer is SiO 2 ;

[0028] The surface of the carrier is grafted with functional groups;

[0029] Wherein, the average particle size of the magnetic nano noble metal catalyst is 30-100nm;

[0030] The magnetic nano noble metal catalyst is used for hydrogenation reaction of nitrile rubber.

[0031] In the present invention, the magnetic nano noble metal catalyst is SiO 2 The coated magnetic nanoparticles are used as carriers, and functional groups are grafted on the surface of the carriers, which can be tightly combined with the precious metal components, and the precious metal components are not easy to fall off. In addition, since the average particle size of the magnetic nano precious metal catalyst is appropriate, the contact efficiency with the reactants can be improved and agglomeration can be avoided, thereby having higher catalytic activity and cyclic stability.

[0032] Furthermore, due to the presence of magnetic nanoparticles in the magnetic nano noble metal catalyst, magnetic separation is easy.

[0033] According to the present invention, the saturation magnetization intensity of the magnetic nano noble metal catalyst is 5-30emu / g, preferably 5-20emu / g.

[0034] According to the present invention, the thickness of the coating layer is 5-50 nm, preferably 8-45 nm.

[0035] According to the present invention, the functional group is selected from at least one of a thiol group, a thiourea group, an amino group, a carboxyl group, an ester group, a hydroxyl group, a carbonyl group, an amide group, a phosphate group and an ether group.

[0036] In the present invention, the functional groups are selected from the above types, which can further improve the binding force with the noble metal component and improve the cyclic stability of the magnetic nano noble metal catalyst.

[0037] Furthermore, the functional group is more preferably a thiol group and a thiourea group.

[0038] According to the present invention, the average particle size of the magnetic nano noble metal catalyst is 50-100 nm;

[0039] According to the present invention, the average particle size of the magnetic nanoparticles is 5-50 nm, and the saturation magnetization is 5-50 emu / g.

[0040] In the present invention, when the average particle size and saturation magnetization intensity of the magnetic nanoparticles meet the above ranges, agglomeration can be avoided and a large specific surface area can be provided, while ensuring high separation efficiency during magnetic separation.

[0041] In the present invention, the average particle size of the magnetic nano noble metal catalyst is greater than the average particle size of the magnetic nano particles.

[0042] According to the present invention, the magnetic nanoparticles are selected from Fe 3 O 4 At least one of Fe nanoparticles, Fe nanoparticles and Co nanoparticles.

[0043] In the present invention, the magnetic nanoparticles are prepared by at least one of a chemical coprecipitation method, a hydrothermal method, a microemulsion method and a sol-gel method.

[0044] In the present invention, the magnetic nanoparticles are prepared by the following method:

[0045] a. FeCl 3 6H 2 O is dissolved in ethylene glycol, sodium acetate and polyethylene glycol are added, stirred evenly, and then placed at 180-220°C for 15-25h (where FeCl 3 6H 2O, sodium acetate and polyethylene glycol (mass ratio is 1:2.4-4.5:0.4-1.1) to obtain a solid;

[0046] b. The obtained solid was washed with deionized water and ethanol to obtain Fe 3 O 4 The nanoparticles are dispersed in a solvent for later use.

[0047] In the present invention, in order to achieve better technical effects, the magnetic nanoparticles are preferably added in the form of a dispersion. There is no particular limitation on the solvent in the dispersion. In order to facilitate the subsequent coating of the magnetic nanoparticles, the solvent is preferably an alcohol solvent, such as ethanol, ethylene glycol, etc.

[0048] In the present invention, the content of the magnetic nanoparticles in the dispersion is 0.005-0.02 g / ml.

[0049] According to the present invention, based on the total weight of the magnetic nano-precious metal catalyst, the content of the precious metal component is 0.5-4wt%.

[0050] In the present invention, when the content of the noble metal component meets the above range, the catalytic activity can be improved, thereby increasing the degree of hydrogenation.

[0051] According to the present invention, based on the total weight of the magnetic nano-precious metal catalyst, the content of the precious metal component is 2-4wt%.

[0052] According to the present invention, the noble metal component is selected from at least one of rhodium, ruthenium and palladium.

[0053] According to the present invention, when the magnetic nano noble metal catalyst is used for hydrogenation of nitrile rubber, after being recycled for 10 times, the hydrogenation degree of the nitrile rubber is not less than 80%, preferably not less than 90%.

[0054] The second aspect of the present invention provides a method for preparing a magnetic nano-precious metal catalyst, characterized in that the method comprises:

[0055] S1, coating the magnetic nanoparticles with a coating agent to obtain magnetic composite nanoparticles;

[0056] S2. In the presence of a solvent, reacting the magnetic composite nanoparticles, a coupling agent, and a functional compound to obtain functional magnetic composite nanoparticles;

[0057] S3, contacting the functional magnetic composite nanoparticles with a metal source to obtain a magnetic nano noble metal catalyst.

[0058] In the present invention, the preparation method is simple, coating the magnetic nanoparticles can avoid agglomeration, and the functional composite magnetic nanoparticles adsorb metal sources through complexation with functional compounds to improve the binding ability to the metal source, thereby further making the catalyst have excellent cyclic stability.

[0059] In the present invention, in step S1, the average particle size of the magnetic composite nanoparticles is 30-100 nm, and the saturation magnetization is 5-30 emu / g.

[0060] Furthermore, the average particle size of the magnetic composite nanoparticles is 50-100 nm, and the saturation magnetization is 5-20 emu / g.

[0061] In the present invention, there is no particular limitation on the solvent in step S2, and it may be, for example, conventional solvents such as toluene and N,N-dimethylformamide in the art, and those skilled in the art may adjust it according to actual needs.

[0062] In the present invention, there is no particular limitation on the coupling agent in step S2, and it may be, for example, chloropropyltriethoxysilane.

[0063] In the present invention, in step S3, the contacting conditions include: stirring at 20-30° C. for 1-4 hours.

[0064] In the present invention, the product obtained by contacting the functional magnetic composite nanoparticles with the rhodium chloride solution is preferably washed and dried.

[0065] Furthermore, there is no particular limitation on the washing and drying conditions, and the washing and drying conditions may be conventional washing and drying methods in the art.

[0066] According to the present invention, the magnetic nanoparticles are prepared by at least one of a chemical coprecipitation method, a hydrothermal method, a microemulsion method and a sol-gel method.

[0067] In the present invention, the preparation of the magnetic nanoparticles is preferably consistent with the method described in the first aspect, which will not be described in detail.

[0068] According to the present invention, the coating is selected from at least one of a sol-gel method, a reverse microemulsion method, an aerosol high-temperature decomposition method, an ultrasonic synthesis method and a template method.

[0069] According to the present invention, the coating is performed by the following method: a coating agent, an alkaline substance and deionized water are added to a magnetic nanoparticle dispersion to react and obtain magnetic composite nanoparticles.

[0070] In the present invention, the method further comprises washing and drying the obtained product after coating the magnetic composite nanoparticles.

[0071] In the present invention, there is no particular limitation on the washing and drying conditions, and the washing and drying conditions may be conventional washing and drying methods in the art.

[0072] In the present invention, the alkaline substance is selected from at least one of aqueous ammonia, sodium hydroxide and potassium hydroxide, preferably aqueous ammonia.

[0073] In the present invention, the alkaline substance is preferably concentrated ammonia water with a mass fraction of 27 wt%.

[0074] According to the present invention, the volume ratio of the magnetic nanoparticle dispersion: coating agent: alkaline substance: deionized water is 1:0.01-0.5:0.02-1:0.2-1, preferably 1:0.05-0.2:0.5-1:0.25-0.8.

[0075] According to the present invention, the coating agent is selected from ethyl orthosilicate and / or methyl orthosilicate.

[0076] According to the present invention, the functional compound is selected from compounds containing at least one functional group selected from the group consisting of thiol, thiourea, amino, carboxyl, ester, hydroxyl, carbonyl, amide, phosphoric acid and ether.

[0077] In the present invention, the functional compound contains the above-mentioned functional group, which can improve the ability to combine with the precious metal component and further improve the catalytic activity and cyclic stability.

[0078] In the present invention, the functional compound is preferably a compound containing at least one functional group of a mercapto group and a thiourea group.

[0079] In the present invention, the mass ratio of the magnetic nanoparticles to the coating agent satisfies the above range, and magnetic composite nanoparticles with a suitable particle size can be obtained.

[0080] In the present invention, in step S2, preferably a stepwise reaction is used. Specifically, the magnetic composite nanoparticles and the coupling agent are first subjected to a first reaction to obtain coupled magnetic composite nanoparticles, and then the coupled magnetic composite nanoparticles and the functional compound are subjected to a second reaction in the presence of NaH to obtain functional magnetic composite nanoparticles.

[0081] In the present invention, the molar ratio of the magnetic composite nanoparticles to the coupling agent is 1:0.02-0.2 based on silicon dioxide.

[0082] In the present invention, the molar ratio of the magnetic composite microspheres calculated as silicon dioxide, the functional compound calculated as functional groups and NaH is 1:0.1-1:0.1-2.

[0083] In the present invention, the conditions of the first reaction include: temperature 120-160° C., time 30-60 h.

[0084] In the present invention, the conditions of the second reaction include: temperature 70-100° C., time 30-60 h.

[0085] In the present invention, the first reaction and the second reaction are preferably carried out in an organic solvent, for example, the organic solvent may be toluene and / or N,N-dimethylformamide.

[0086] According to the present invention, the dosage of the functional composite magnetic nanoparticles and the metal source is such that the content of the noble metal component in the magnetic nano noble metal catalyst is 0.5-4wt%, preferably 2-4wt%.

[0087] In the present invention, when the content of the noble metal component in the functional magnetic composite nanoparticles meets the above range, the prepared magnetic nano noble metal catalyst has a higher catalytic activity.

[0088] According to the present invention, the metal source is selected from at least one of rhodium chloride, ruthenium chloride and palladium chloride.

[0089] The third aspect of the present invention provides a method for preparing hydrogenated nitrile rubber, characterized in that the method comprises: contacting nitrile rubber glue, a magnetic nano-precious metal catalyst and a phosphine ligand, and performing a hydrogenation reaction to obtain a hydrogenated nitrile rubber glue;

[0090] Wherein, the magnetic nano noble metal catalyst is the magnetic nano noble metal catalyst provided by the first aspect of the present invention or the magnetic nano noble metal catalyst prepared by the method provided by the second aspect of the present invention;

[0091] The content of the noble metal element in the magnetic nano noble metal catalyst is 0.008-0.03wt% of the dry nitrile rubber.

[0092] In the present invention, the method for preparing hydrogenated nitrile rubber is simple and easy to implement. After the hydrogenation reaction is completed, the magnetic nano noble metal catalyst can be separated from the reaction system by magnetic separation.

[0093] In the present invention, the magnetic nano noble metal catalyst can be recycled for 10 times or more without obvious deactivation and has excellent cycle stability.

[0094] In the present invention, the nitrile rubber solution comprises nitrile rubber and an organic solvent.

[0095] In the present invention, the organic solvent is selected from at least one of aromatic hydrocarbons, derivatives of aromatic hydrocarbons substituted by alkyl or halogen, halogenated alkanes, ethers, ketones and amides.

[0096] Furthermore, the organic solvent is at least one of benzene, toluene, xylene, chlorobenzene, dichlorobenzene, trichlorobenzene, dichloromethane, chloroform, 1,2-dichloroethane, tetrahydrofuran, acetone, butanone and N,N-dimethylformamide.

[0097] According to the present invention, the solid content of the nitrile rubber solution is 1-15wt%.

[0098] In the present invention, in the nitrile rubber solution, when the solid content of the nitrile rubber solution meets the above range, the viscosity of the solution is more suitable for hydrogenation reaction.

[0099] According to the present invention, the solid content of the nitrile rubber solution is 3-10wt%.

[0100] According to the present invention, the phosphine ligand is at least one selected from triphenylphosphine, triethylphosphine, ethyldiphenylphosphine and diethylphenylphosphine.

[0101] According to the present invention, the amount of the phosphine ligand added is 0.02-1.5 wt % of the nitrile rubber dry rubber, calculated as phosphorus.

[0102] In the present invention, when the amount of the phosphine ligand added meets the above range, the catalytic activity can be further improved.

[0103] According to the present invention, the amount of the phosphine ligand added is 0.05-1 wt % of the dry nitrile rubber, calculated as phosphorus.

[0104] According to the present invention, the content of the noble metal element in the magnetic nano noble metal catalyst is 0.01-0.02wt% of the dry nitrile rubber.

[0105] In the present invention, the content of rhodium in the magnetic nano noble metal catalyst satisfies the above range, which can further improve the degree of hydrogenation.

[0106] According to the present invention, the conditions of the hydrogenation reaction include: pressure 1-10 MPa, temperature 70-150° C., and time 1-18 h.

[0107] In the present invention, when the conditions of the hydrogenation reaction meet the above range, the hydrogenation degree of the nitrile rubber is further improved by synergistic effect with the magnetic nano noble metal catalyst.

[0108] According to the present invention, the conditions of the hydrogenation reaction include: pressure 3-8 MPa, temperature 80-150° C., and time 4-12 h.

[0109] The fourth aspect of the present invention provides a hydrogenated nitrile rubber prepared by the method provided by the third aspect of the present invention, characterized in that when the magnetic nano noble metal catalyst is used once, the hydrogenation degree of the hydrogenated nitrile rubber is not less than 80%;

[0110] Alternatively, when the magnetic nano noble metal catalyst is used 10 times, the degree of hydrogenation of the hydrogenated nitrile rubber is not less than 80%.

[0111] Preferably, when the magnetic nano noble metal catalyst is used once, the degree of hydrogenation of hydrogenated nitrile rubber is not less than 90%;

[0112] Alternatively, when the magnetic nano noble metal catalyst is used 10 times, the hydrogenation degree of the hydrogenated nitrile rubber is not less than 90%.

[0113] The fifth aspect of the present invention provides an application of the hydrogenated nitrile rubber described in the fourth aspect of the present invention in at least one of the fields of aerospace, oil fields, transportation and deep sea.

[0114] The present invention will be described in detail below through examples.

[0115] In the following examples, the degree of hydrogenation was measured by HNMR;

[0116] Rhodium chloride was purchased from Kunming Borui Metal Materials Co., Ltd.;

[0117] NaH, 60 wt%, dispersed in mineral oil;

[0118] The saturation magnetization was measured using a vibrating sample magnetometer (model 7307) from Lake Shore, USA;

[0119] Nitrile rubber was purchased from PetroChina Lanzhou Petrochemical Company, brand 4105;

[0120] FeCl 3 6H 2 O, ethylene glycol, sodium acetate, polyethylene glycol, ethanol, cyclohexane, tert-octylphenol polyoxyethylene ether, ammonium hydroxide, chloropropyltriethoxysilane, thiourea, N,N-dimethylformamide, ethyl ether, triphenylphosphine, chlorobenzene, and tetraethyl orthosilicate were all commercially available analytical grade chemicals.

[0121] The magnetic nanoparticles used in the present invention are prepared according to the following method

[0122] a. Add 20gFeCl 3 6H 2 O was dissolved in 200 mL of ethylene glycol, and 54 g of sodium acetate and 15 g of polyethylene glycol were added. 3 6H 2 The mass ratio of O, sodium acetate and polyethylene glycol is 1:2.7:0.75. After stirring evenly, place at 200°C for reaction for 20 hours, and filter to obtain a solid;

[0123] b. Wash the obtained solid with deionized water and ethanol to obtain Fe 3 O4 Nanoparticles with an average particle size of 12 nm and a saturation magnetization of 27 emu / g were dispersed in ethanol to obtain Fe 3 O 4 Dispersion (Fe 3 O 4 The content is 1wt%).

[0124] The following preparation example is used to describe the preparation of magnetic composite nanoparticles

[0125] Preparation Example 1

[0126] The 100 mL Fe 3 O 4 The dispersion was stirred and mixed evenly with 5.5 mL of tetraethyl orthosilicate, 30 mL of concentrated ammonia water (27 wt%) and 45 mL of deionized water, and then sealed for reaction for 4 hours. The resulting product was washed with deionized water and ethanol to obtain magnetic composite nanoparticles Y-1, whose average particle size, coating layer thickness and saturation magnetization are shown in Table 1.

[0127] Preparation Example 2

[0128] The method is consistent with that of Preparation Example 1, except that the amount of concentrated ammonia water (27 wt %) used is 100 mL. Magnetic composite nanoparticles Y-2 are obtained, and the average particle size, coating layer thickness and saturation magnetization thereof are shown in Table 1.

[0129] Preparation Example 3

[0130] The method is consistent with that of Preparation Example 1, except that the amount of deionized water used is 30 mL. Magnetic composite nanoparticles Y-3 are obtained, and the average particle size, coating layer thickness and saturation magnetization thereof are shown in Table 1.

[0131] Preparation Example 4

[0132] The method is consistent with that of Preparation Example 1, except that the amount of deionized water used is 5 mL. Magnetic composite nanoparticles Y-4 are obtained, and the average particle size, coating layer thickness and saturation magnetization thereof are shown in Table 1.

[0133] Comparative Preparation Example 1

[0134] The method is consistent with that of Preparation Example 1, except that the amount of deionized water used is 80 mL, and the amount of concentrated ammonia water (27 wt %) used is 80 mL. Magnetic composite nanoparticles DY-1 are obtained, and their average particle size, coating layer thickness and saturation magnetization are shown in Table 1.

[0135] Table 1

[0136] type Average particle size (nm) Average coating thickness (nm) Saturation magnetization (emu / g) Y-1 62 25 11.5 Y-2 96 42 12 Y-3 48 18 11.3 Y-4 27 7.5 10.2 DY-1 400 194 4.9

[0137] The following preparation example is used to illustrate the preparation of magnetic nano-precious metal catalysts.

[0138] Preparation Example 5

[0139] S1. In the presence of 100 mL of toluene, 1 g of the magnetic composite nanoparticles Y-1 prepared in Preparation Example 1 and 0.1 g of chloropropyltriethoxysilane were stirred and refluxed at 150° C. for 30 h, followed by centrifugal separation to obtain coupled magnetic composite nanoparticles, wherein the molar ratio of the magnetic composite nanoparticles to the coupling agent based on silicon dioxide was 1:0.03. The coupled magnetic composite nanoparticles were fully washed with ethanol and then dried in a vacuum drying oven at 90° C. for 6 h.

[0140] 1 g of coupled magnetic composite nanoparticles, 0.2 g of thiourea and NaH solution (containing 0.05 g of NaH) were added to 10 mL of N,N-dimethylformamide, stirred and refluxed at 80°C for 48 hours, and then centrifuged. The product was fully washed with ethanol and dried in a vacuum drying oven at 100°C for 12 hours to obtain functional magnetic composite nanoparticles, wherein the molar ratio of the magnetic composite microspheres based on silica, the functional compound based on the functional group and NaH was 1:0.16:0.13.

[0141] S2. 0.1 g of the above-mentioned functional magnetic composite nanoparticles was contacted with 10 mL of rhodium chloride aqueous solution (containing 0.008 g of rhodium chloride), stirred at 25°C for 2 h, and the product was fully washed with acetone and dried at 100°C for 3 h to obtain the magnetic nano precious metal catalyst Cat-1.

[0142] Among them, the average particle size, type of functional group, content of precious metal component, and saturation magnetization intensity of the magnetic nano-precious metal catalyst Cat-1 are shown in Table 2.

[0143] Preparation Example 6-8

[0144] The method is consistent with that of Preparation Example 5, except that the magnetic composite nanoparticles obtained in Preparation Example 1 are replaced by the magnetic composite nanoparticles obtained in Preparation Examples 2-4 to obtain magnetic nano noble metal catalysts Cat-2-Cat-4.

[0145] The average particle size, type of functional group, content of precious metal component, and saturation magnetization of the magnetic nano-precious metal catalysts Cat-2 to Cat-4 are shown in Table 2.

[0146] Preparation Example 9

[0147] The method is consistent with that of Preparation Example 5, except that in step S2, the amount of rhodium chloride used is 0.004 g;

[0148] The average particle size, type of functional group, content of precious metal component, and saturation magnetization of the obtained magnetic nano-precious metal catalyst Cat-5 are shown in Table 2.

[0149] Preparation Example 10

[0150] The method is consistent with that of Preparation Example 5, except that thiourea is replaced by aniline.

[0151] The average particle size, type of functional group, content of precious metal component and saturation magnetization of the obtained magnetic nano-precious metal catalyst Cat-6 are shown in Table 2.

[0152] Comparative Preparation Example 2

[0153] The method is consistent with that of Preparation Example 5, except that in step S2, the functional magnetic composite nanoparticles are replaced with the magnetic composite nanoparticles Y-1 prepared in Preparation Example 1;

[0154] The average particle size, type of functional group, content of precious metal component and saturation magnetization of the obtained magnetic nano-precious metal catalyst Cat-D1 are shown in Table 2.

[0155] Comparative Preparation Example 3

[0156] The method is consistent with that of Preparation Example 5, except that in step S1, the magnetic composite nanoparticles Y-1 are replaced with silica nanoparticles;

[0157] The average particle size, type of functional group, content of precious metal component and saturation magnetization of the obtained magnetic nano-precious metal catalyst Cat-D2 are shown in Table 2.

[0158] Comparative Preparation Example 4

[0159] The method is consistent with that of Preparation Example 5, except that the magnetic composite nanoparticles obtained in Preparation Example 1 are replaced by the magnetic composite nanoparticles obtained in Comparative Preparation Example 1;

[0160] The average particle size, type of functional group, content of precious metal component and saturation magnetization of the obtained magnetic nano-precious metal catalyst Cat-D3 are shown in Table 2.

[0161] Table 2

[0162]

[0163] The following examples are used to describe the method of applying the above magnetic nano noble metal catalyst to hydrogenation of nitrile rubber solution.

[0164] Example 1

[0165] Under nitrogen protection, 50g of nitrile rubber was dissolved in 575g of chlorobenzene solution, 1g of magnetic nano noble metal catalyst Cat-1 and 800mg of triphenylphosphine were added thereto, the temperature was raised to 110°C, and the hydrogen pressure was 6MPa, and the reaction was carried out for 5 hours, and the temperature and pressure were lowered to obtain hydrogenated nitrile rubber liquid, and hydrogenated nitrile rubber was separated;

[0166] Among them, the type of the magnetic nano noble metal catalyst, the amount of the magnetic nano noble metal catalyst a , the type of phosphine ligand, the amount of phosphine ligand added b The solid content, hydrogenation temperature, hydrogenation pressure and hydrogenation time of the nitrile rubber solution are shown in Table 3, and the degree of hydrogenation is shown in Table 4.

[0167] Examples 2-18, Comparative Examples 1-3

[0168] The method is consistent with that of Example 1, except that the type and amount of the magnetic nano noble metal catalyst are a , Type of phosphine ligand, amount of phosphine ligand b The solid content, hydrogenation temperature, hydrogenation pressure and hydrogenation time of the nitrile rubber solution are as shown in Table 3, and the degree of hydrogenation is shown in Table 4.

[0169] Table 3

[0170]

[0171] Note: a It refers to the mass fraction of rhodium element in the catalyst to nitrile rubber; b It refers to the mass fraction of phosphine ligands in nitrile rubber.

[0172] Table 4

[0173]

[0174]

[0175] In order to further test the cycle stability, the magnetic nano-precious metal catalysts Cat-1, Cat-4 and Cat-D1 were cycled for 5 and 10 times respectively, and the hydrogenation degrees are shown in Table 5:

[0176] Table 5

[0177] serial number Hydrogenation degree / % Cat-1 is used for 5 times 96.1 Cat-1 is used 10 times 96.1 Cat-4 is used 5 times 90.4 Cat-4 is used 10 times 90.2 Cat-D1 is used for 5 times 45 Cat-D1 is used 10 times 11.4

[0178] According to the above data, it can be seen that the magnetic nano precious metal catalyst provided by the present invention has good technical effects, and the degree of hydrogenation is above 80%. The embodiments of the preferred technical scheme provided by the present invention obviously obtain better technical effects, and the degree of hydrogenation is not less than 90%. Among them, after the magnetic nano precious metal catalysts Cat-1 and Cat-4 were recycled 10 times respectively, the degree of hydrogenation did not decrease significantly, and the more preferred magnetic nano precious metal catalyst Cat-1 was recycled for more than 10 times without any deactivation, and the degree of hydrogenation was still maintained above 95%.

[0179] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A magnetic nano noble metal catalyst, characterized in that: The magnetic nano noble metal catalyst comprises a carrier and a noble metal component loaded on the surface of the carrier; The carrier comprises a substrate and a coating layer; Wherein, the matrix is ​​magnetic nanoparticles, and the coating layer is SiO2; The surface of the carrier is grafted with functional groups; The average particle size of the magnetic nano noble metal catalyst is 30-100 nm; The magnetic nano noble metal catalyst is used for hydrogenation reaction of nitrile rubber.

2. The magnetic nano noble metal catalyst according to claim 1, wherein: The saturation magnetization of the magnetic nano noble metal catalyst is 5-30emu / g, preferably 5-20emu / g; Preferably, the coating layer has a thickness of 5-50 nm, preferably 8-45 nm.

3. The magnetic nano noble metal catalyst according to claim 1 or 2, wherein: The functional group is selected from at least one of a thiol group, a thiourea group, an amino group, a carboxyl group, an ester group, a hydroxyl group, a carbonyl group, an amide group, a phosphate group and an ether group; Preferably, the average particle size of the magnetic nano noble metal catalyst is 50-100 nm; Preferably, the average particle size of the magnetic nanoparticles is 5-50 nm, and the saturation magnetization is 5-50 emu / g; Preferably, the magnetic nanoparticles are selected from at least one of Fe3O4 nanoparticles, Fe nanoparticles and Co nanoparticles.

4. The magnetic nano noble metal catalyst according to any one of claims 1 to 3, wherein: Based on the total weight of the magnetic nano noble metal catalyst, the content of the noble metal component is 0.5-4wt%, preferably 2-4wt%; Preferably, the noble metal component is selected from at least one of rhodium, ruthenium and palladium.

5. The magnetic nano noble metal catalyst according to any one of claims 1 to 4, wherein: When the magnetic nano noble metal catalyst is used for hydrogenation of nitrile rubber, after being recycled for 10 times, the hydrogenation degree of the nitrile rubber is not less than 80%, preferably not less than 90%.

6. A method for preparing a magnetic nano-precious metal catalyst, characterized in that: The method comprises: S1, coating the magnetic nanoparticles with a coating agent to obtain magnetic composite nanoparticles; S2. In the presence of a solvent, reacting the magnetic composite nanoparticles, a coupling agent and a functional compound to obtain functional magnetic composite nanoparticles; S3, contacting the functional magnetic composite nanoparticles with a metal source to obtain a magnetic nano noble metal catalyst.

7. The method according to claim 6, wherein: The magnetic nanoparticles are prepared by at least one of a chemical coprecipitation method, a hydrothermal method, a microemulsion method and a sol-gel method; Preferably, the coating is selected from at least one of a sol-gel method, a reverse microemulsion method, an aerosol high-temperature decomposition method, an ultrasonic synthesis method and a template method; Preferably, the coating is performed by the following method: dispersing the magnetic nanoparticles in alcohol to generate a magnetic nanoparticle dispersion, adding a coating agent and deionized water in the presence of an alkaline substance to react to obtain magnetic composite nanoparticles; Preferably, the volume ratio of the magnetic nanoparticle dispersion: coating agent: alkaline substance: deionized water is 1:0.01-0.5:0.02-1:0.2-1, preferably 1:0.05-0.2:0.5-1:0.25-0.

8.

8. The method according to claim 6 or 7, wherein: The coating agent is selected from ethyl orthosilicate and / or methyl orthosilicate; Preferably, the functional compound is selected from compounds containing at least one functional group selected from the group consisting of thiol, thiourea, amino, carboxyl, ester, hydroxyl, carbonyl, amide, phosphate and ether; Preferably, the molar ratio of the magnetic composite nanoparticles, the coupling agent and the functional compound is 1:0.02-0.2:0.1-1 calculated on the basis of silicon dioxide; Preferably, the amount of the functional composite magnetic nanoparticles and the metal source is such that the content of the noble metal component in the magnetic nano noble metal catalyst is 0.5-4wt%, preferably 2-4wt%; Preferably, the metal source is selected from at least one of rhodium chloride, ruthenium chloride and palladium chloride.

9. A method for preparing hydrogenated nitrile rubber, characterized in that: The method comprises: contacting a nitrile rubber liquid, a magnetic nano noble metal catalyst and a phosphine ligand, and performing a hydrogenation reaction to obtain a hydrogenated nitrile rubber liquid; Wherein, the magnetic nano noble metal catalyst is the magnetic nano noble metal catalyst described in any one of claims 1 to 5 or the magnetic nano noble metal catalyst prepared by the method described in any one of claims 6 to 8; The content of the noble metal component in the magnetic nano noble metal catalyst is 0.008-0.03wt% of the dry nitrile rubber.

10. The method according to claim 9, wherein: The solid content of the nitrile rubber solution is 1-15wt%, preferably 3-10wt%; Preferably, the phosphine ligand is selected from at least one of triphenylphosphine, triethylphosphine, ethyldiphenylphosphine and diethylphenylphosphine; Preferably, the amount of the phosphine ligand added is 0.02-1.5wt% of the nitrile rubber dry rubber, preferably 0.05-1wt% based on phosphorus; Preferably, the content of the noble metal element in the magnetic nano noble metal catalyst is 0.01-0.02wt% of the nitrile rubber dry rubber.

11. The method according to claim 9 or 10, wherein: The conditions of the hydrogenation reaction include: pressure of 1-10 MPa, preferably 3-8 MPa; temperature of 70-150° C., preferably 80-150° C.; reaction time of 1-18 h, preferably 4-12 h.

12. A hydrogenated nitrile rubber prepared by the method according to any one of claims 9 to 11, characterized in that: When the magnetic nano noble metal catalyst is used once, the degree of hydrogenation of hydrogenated nitrile rubber is not less than 80%; Alternatively, when the magnetic nano noble metal catalyst is used 10 times, the degree of hydrogenation of the hydrogenated nitrile rubber is not less than 80%.

13. Use of the hydrogenated nitrile rubber according to claim 12 in at least one of the fields of aerospace, oil field, transportation and deep sea.